1997
DOI: 10.1111/j.1600-0447.1997.tb10144.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the psychobiology of social phobia: personality domains and serotonergic function

Abstract: The aim of the present study was to explore a psychobiological perspective in the aetiology of social phobia. The emphasis was on serotonergic function and personality. A total of 20 social phobics according to ICD-10 DCR criteria were assessed with the Schedule for Clinical Assessment in Neuropsychiatry and the International Personality Disorder Examination. They were compared with an age-matched normal population with regard to scores on the Fear of Negative Evaluation Scale, the Social Avoidance and Distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 33 publications
3
36
1
1
Order By: Relevance
“…The present findings converge with those previously reported using the KSP, where high scores on anxiety scales were associated with social phobia (7), as well as with those using the revised NEO Personality Inventory, where high neuroticism and low extraversion were revealed in social phobics (30). Also, the present results are largely in accordance with those reported previously for TCI personality dimensions in social phobia (22). The only differences between the studies is that Chatterjee et al (22) noted lower Novelty seeking in social phobics but not lower Persistence, as was found in our investigation.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…The present findings converge with those previously reported using the KSP, where high scores on anxiety scales were associated with social phobia (7), as well as with those using the revised NEO Personality Inventory, where high neuroticism and low extraversion were revealed in social phobics (30). Also, the present results are largely in accordance with those reported previously for TCI personality dimensions in social phobia (22). The only differences between the studies is that Chatterjee et al (22) noted lower Novelty seeking in social phobics but not lower Persistence, as was found in our investigation.…”
Section: Discussionsupporting
confidence: 95%
“…Also, the present results are largely in accordance with those reported previously for TCI personality dimensions in social phobia (22). The only differences between the studies is that Chatterjee et al (22) noted lower Novelty seeking in social phobics but not lower Persistence, as was found in our investigation. This inconsistency may be due to the high Axis I comorbidity (75%) in the former study.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The vertical lines represent the overall result of meta-analysis. Names of first authors refer to the following references: Mertol [30], Mula [31], Wachleski [32], Marchesi [33], Battaglia [37], Wiborg [35], Cowley [40], Saviotti [41], Mörtberg [45], Lochner [46], Marteinsdottir [49], Pelissolo [50], Kim (1996) [51], Chatterjee [52], Faytout [47], Kim (2009) [53], Alonso [57], Cruz-Fuentes [58], Lyoo [59], Kusunoki [61], Richter [62], Pfohl [63], Ettelt [56]. …”
Section: Resultsmentioning
confidence: 99%
“…The 100-item Tridimensional Personality Questionnaire (TPQ; Cloninger, 1987a,b) was designed to measure harm avoidance and two other personality traits-novelty seeing and reward dependence. Several studies have reported greater harm avoidance in individuals with SAD when compared to controls (Chatterjee, Sunitha, Velayudhan, & Khanna, 1997;Marteinsdottir, Tillfors, Furmark, Anderberg, & Ekselius, 2003;.…”
Section: Introductionmentioning
confidence: 99%